In-Depth Sequence Analysis of Bread Wheat VRN1 Genes - Strejčková, Beáta; Milec, Zbyněk; Holušová, Kateřina; Cápal, Petr; Vojtková, Tereza; Čegan, Radim; Šafář, Jan (International journal of molecular sciences, 2021)
The VERNALIZATION1 (VRN1) gene encodes a MADS-box transcription factor and plays an important role in the cold-induced transition from the vegetative to reproductive stage. Allelic variability of VRN1 homoeologs has been associated with large differences in flowering time. The aim of this study was to investigate the genetic variability of VRN1 homoeologs (VRN-A1, VRN-B1 and VRN-D1). We performed an in-depth sequence analysis of VRN1 homoeologs in a panel of 105 winter and spring varieties of hexaploid wheat. We describe the novel allele Vrn-B1f with an 836 bp insertion within intron 1 and show its specific expression pattern associated with reduced heading time. We further provide the complete sequence of the Vrn-A1b allele, revealing a 177 bp insertion in intron 1, which is transcribed into an alternative splice variant. Copy number variation (CNV) analysis of VRN1 homoeologs showed that VRN-B1 and VRN-D1 are present in only one copy. The copy number of recessive vrn-A1 ranged from one to four, while that of dominant Vrn-A1 was one or two. Different numbers of Vrn-A1a copies in the spring cultivars Branisovicka IX/49 and Bastion did not significantly affect heading time. We also report on the deletion of secondary structures (G-quadruplex) in promoter sequences of cultivars with more vrn-A1 copies.
Keywords: Gene Dosage; VRN1; Triticum; represorové proteiny; chléb; alternative splice variants; genetická variace; Sequence Analysis, DNA; genová dávka; sekvenční analýza DNA; pšenice; CNV; Bread; alternativní sestřih; allelic variation; inzerční mutageneze; Repressor Proteins; Alternative Splicing; Polyploidy; Alleles; Genetic Variation; alely; wheat; Mutagenesis, Insertional; next generation sequencing; polyploidie